Flexible Working terhadap Employee Achievement: Peran Mediasi Work-Life Balance pada Kurir - Aqil, Muhammad; Ramli S, Ramli S; Dahri, Nur Wahyunianti; Yeni, Hari; Rasyid, Rohsita Amalyah (Journal of Management Branding, 2024)
A courier is someone who is tasked with delivering packages in the form of documents or other items to individuals, businesses, institutions, or government agencies. Courier is not a new profession. This job has existed since ancient times, when people would run to deliver messages or items to someone. From there, the word courier emerged in English, which comes from the Greek word curere, meaning to run. Some issues that arise include the lack of flexible working arrangements, which is why work-life balance is introduced here as a bridge to enhance employee achievements by implementing a flexible working system. This study aims to confirm the influence of flexible working on employee achievements mediated by work-life balance among couriers in Mamuju. This study uses a quantitative approach to analyze data related to the variables whose relationships will be examined. This study used a sample of 100 respondents with snowball sampling technique using SEM (Structural Equation Modelling). The results of this study show that flexible working does not affect employee achievement, flexible working does not affect work-life balance, work-life balance affects employee achievement, and work-life balance does not directly mediate the relationship between flexible working and employee achievement